Using PhotoVoice as an Evaluation Method - Hunter, Ouen; Leeburg, Emma; Harnar, Michael (Journal of MultiDisciplinary Evaluation, 2020)
Background: Engaging with youth through PhotoVoice is beneficial as a program evaluation method and functions as a method of inquiry to understand youths’ perceptions of a college preparation program. The students used PhotoVoice to respond to prompts about how they learn and their opinions of the college preparation program. Purpose: This reflection of practice article provides an example of PhotoVoice as an evaluation method. Setting: This evaluation was conducted during the summer college preparation programming. Intervention: The combination of student photography, photo gallery walk, and group discussion as an evaluation method. Research Design: A qualitative reflective design. Data Collection and Analysis: The student photographs, narratives, and observational notes were analyzed thematically. Findings: We found that the youths enjoyed the unique experience of PhotoVoice. The combination of student photography, narratives, gallery walk, and group discussion, were useful as an inquiry tool for this youth program.